english english - Siti Mayasari Pakaya; Intan Tiara Kartika; Muhammad Akram Mursalim; Abdul Wahab Thomas (LP2M Universitas Sarjanawiyata Tamansiswa, 2026)
This study examines the role of digital micro, small, and medium enterprises (MSMEs) in advancing Indonesia’s Sustainable Development Goals (SDGs), focusing on three interrelated issues: digital inclusivity, access inequality, and platform market dominance. Adopting a qualitative descriptive approach through library-based research, the study analyses secondary data from journal articles, international agency reports, official government publications, and statistical sources from 2019 to 2025. Data analysis employed thematic synthesis supported by NVivo 12 Plus for coding, theme identification, and word cloud visualisation. The findings reveal that digitalisation contributes to inclusive economic participation and women’s entrepreneurship, aligning with SDG 8 (Decent Work and Economic Growth). However, persistent infrastructure disparities, uneven broadband distribution, and limited digital literacy—particularly in rural regions—continue to constrain equitable access, impeding progress toward SDG 9 (Industry, Innovation, and Infrastructure). Moreover, the dominance of a few e-commerce platforms such as Tokopedia and Shopee reinforces market dependency and unequal power relations, counteracting the objectives of SDG 10 (Reduced Inequalities). Applying the Global Political Economy, Capability Approach, and Inclusive Innovation frameworks, the study concludes that realising the SDGs through MSME digitalisation requires oversight of platform power, equitable digital infrastructure, and empowerment of entrepreneurial capabilities. Policy implications include strengthening competition regulation, expanding digital skills programmes, and institutionalising inclusive innovation strategies. Future research should explore comparative and mixed-method studies across ASEAN contexts to validate and deepen these findings.